2021
DOI: 10.24011/barofd.897343
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19'un Türkiye Orman Ürünleri Endüstrisine Etkisi

Abstract: In the present paper the impact of COVID-19 pandemic on Turkish forest products industry was investigated with the help of qualitative research methods. Focus groups and interview methods were adopted as the methodology. The scope of the study is limited to wood-based panel, laminate flooring and furniture industries which are the leading branches within forest products industry of Turkey. The respondents are white-collar workers randomly chosen from engineers, managers or marketing directors of large-sized en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…Yöneticilerin pandeminin olumsuz etkilerine ilişkin öne çıkan görüşleri işgücü kaybı ve iş ve pazar kaybı/mali kayıplar yaşandığı olmuştur. Pandeminin, orman ürünleri endüstrisinin farklı sektörlerinde hammadde tedarik zincirini ve ürün sevkiyatını durdurması (Ratnasingam vd., 2020;Bayram, 2021;Ateş, Enez ve Külçe, 2021), ürünlerin pazarlama platformlarını engellemesi (Ratnasingam vd., 2021) nedeniyle kapasite kaybına ve finansal zararlara yol açtığı bildirilmiştir. Yöneticilerin çoğu olumsuz etkiler ile baş etmek için üretimi yeniden planladıklarını ve devlet/İŞKUR desteğinden faydalandıklarını bildirmişlerdir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Yöneticilerin pandeminin olumsuz etkilerine ilişkin öne çıkan görüşleri işgücü kaybı ve iş ve pazar kaybı/mali kayıplar yaşandığı olmuştur. Pandeminin, orman ürünleri endüstrisinin farklı sektörlerinde hammadde tedarik zincirini ve ürün sevkiyatını durdurması (Ratnasingam vd., 2020;Bayram, 2021;Ateş, Enez ve Külçe, 2021), ürünlerin pazarlama platformlarını engellemesi (Ratnasingam vd., 2021) nedeniyle kapasite kaybına ve finansal zararlara yol açtığı bildirilmiştir. Yöneticilerin çoğu olumsuz etkiler ile baş etmek için üretimi yeniden planladıklarını ve devlet/İŞKUR desteğinden faydalandıklarını bildirmişlerdir.…”
Section: Discussionunclassified
“…Yarı yapılandırılmış olarak hazırlanan görüşme formunun hazırlanmasında daha önceki çalışmalardan yararlanılmıştır (Bayram, 2021;Ateş vd., 2021;Kırklıkçı, 2022). Görüşme formunun yarı yapılandırılmış olarak hazırlanmasının amacı, görüşmeler sırasında öngörülmemiş olan alanlara yönelik bazı ayrıntılamaların kullanılmasına esneklik sağlanmasıdır.…”
Section: Görüşme Formuunclassified
“…Two studies have been carried out in Turkey examining the effects of the pandemic in the forest products industry. The qualitative study of Bayram (2021) on the effects of the COVID-19 pandemic in the forest products industry pointed out the great economic damage caused by stopping the raw material supply chain and product shipment through customs gates and limiting the working hours of employees or dismissing them for economic reasons. In the same study, an evaluation was conducted between January and June 2020 that revealed the results of the first wave of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In the Turkish domestic markets, sales have decreased by 30% due to the Covid-19 restrictions and problems that occurred in the supply of wood-based forest products raw materials (Bayram 2021). In the continuation of the process, it is foreseen that the uncertainty in the supply and demand in the markets will persevere (Ozenc 2020).…”
Section: Peer-reviewed Articlementioning
confidence: 99%
“…In a similar manner, the forest products industry sector was negatively affected by the process. The priority issue for the new possible negative processes of the sector is raw material procurement (Bayram 2021). However, the first studies on the subject have shown that not every business in the sector is affected by the process in the same manner (Yücel and Durak 2021).…”
Section: Introductionmentioning
confidence: 99%